Performance of self-cleaning cotton textiles coated with TiO2, TiO2-SiO2 and TiO2-SiO2-HY in removing Rhodamine B and Reactive Red 120 dyes from aqueous solutions - Landi Jr, Salmon (2021)
In the present study composites based on TiO(2 )nanoparticles, SiO2 and HY zeolite were synthesized by using a standard sol-gel methodology and analyzed by Fourier-transform infrared spectroscopy, X-ray diffraction and scanning electron microscopy-energy-dispersive X-ray spectroscopy techniques. The photocatalysts were impregnated on cotton textiles and their photocatalytic abilities were examined by degradation of Rhodamine B (RhB) and Reactive Red 120 (RR120) dyes in aqueous solution under similar solar irradiation. RhB removal efficiencies from cotton textiles were 87%, 72% and 50% for TiO2, TiO2-SiO2-HY zeolite and TiO2-SiO2 composites, respectively and achieved after 3 h of light irradiation. However, for the RR120 dye, the reached result was different as the photodegradation for this dye (65% efficiency) was only observed in bare TiO2 functionalized textile. In addition, for the treatment with TiO2-SiO2-HY zeolite, it was found that for initial alkaline conditions at pH of the RhB dye solution, the photodegradation rate decreased.